Preparing a Map for the Surface Temperature Distribution of Baghdad andthe Marsh Area Using Remote Sensing Technique - Hadi, Firas; Abdulwahhab, Rawnaq (Iraqi Journal of Science, 2024)
Temperatures are important factors that have an impact directly and indirectly onthe human, so the attention to this aspect certainly will be in the interest of humanlife. It is no secret to anyone increased warming and cause concern in the scientificauthorities. On this basis, interested search to produce digital map and classifiedchromatically for the temperature distribution and by taking advantage of the band 6of the satellite Landsat ETM+ and TM, also introduced in the calculations standardssensor satellite mentioned within emissions equations for the purpose of extractingthis map.Namely, that it is possible to know the temperature of any point in the study sitethrough color classification of this map and easily find out the temperature of thatsite by color groups belonging to that class. As used thermal images belonging to thestudy area for consecutive periods of time for the purpose of knowledge over thedifference in temperatures for that area during a certain period of time, Where theresearch show that the study area (Baghdad in the middle of Iraq and marshes insouthern Iraq) suffering from a rapid increase in temperature, which reflectednegatively on the ecology of the area specially in marshes. The method used inresearch can be applied using ENVI software to any part of the areas of Iraq as soonas you get the thermal band of Landsat ETM+ and TM, this method may lead todetect heat sources unknown and unexpected areas of difficult access and measurethe temperature.